2010
DOI: 10.1094/mpmi-23-7-0846
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Participates in the Complex Interplay of Defense-Related Signaling Pathways Controlling Disease Resistance to Sclerotinia sclerotiorum in Arabidopsis thaliana

Abstract: Studies of the interaction between Arabidopsis thaliana and the necrotrophic fungal pathogen Sclerotinia sclerotiorum have been hampered by the extreme susceptibility of this model plant to the fungus. In addition, analyses of the plant defense response suggested the implication of a complex interplay of hormonal and signaling pathways. To get a deeper insight into this host-pathogen interaction, we first analyzed the natural variation in Arabidopsis for resistance to S. sclerotiorum. The results revealed a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
127
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(138 citation statements)
references
References 98 publications
9
127
2
Order By: Relevance
“…NO a small diffusible molecule is nowadays being recognized as an emerging key signaling molecule in response to broad range of stresses in plants (Neill et al 2003;RomeroPuertas et al 2004;Khan et al 2012). It appears to be an early signaling factor that helps in orchestrating a number of downstream signaling pathways (Perchepied et al 2010). From our laboratory we have reported the correlation between the NO generation and induction of defenserelated molecules due to application of elicitor on tea leaves (Chandra et al 2014b.…”
Section: Discussionmentioning
confidence: 99%
“…NO a small diffusible molecule is nowadays being recognized as an emerging key signaling molecule in response to broad range of stresses in plants (Neill et al 2003;RomeroPuertas et al 2004;Khan et al 2012). It appears to be an early signaling factor that helps in orchestrating a number of downstream signaling pathways (Perchepied et al 2010). From our laboratory we have reported the correlation between the NO generation and induction of defenserelated molecules due to application of elicitor on tea leaves (Chandra et al 2014b.…”
Section: Discussionmentioning
confidence: 99%
“…A link between disease resistance, NO and ROS was also indicated by analysing different Arabidopsis ecotypes after inoculation with Sclerotinia sclerotiorum. Resistant ecotypes showed a higher expression of AtRbohD and F as well as an earlier accumulation of NO and H 2 O 2 when compared to susceptible ecotypes during interaction with S. sclerotiorum (Perchepied et al, 2010). Adding another layer of complexity to the interplay between NO and ROS, AtRbohD function was shown to be negatively regulated by NO-dependent S-nitrosylation during hypersensitive response (Yun et al, 2011).…”
Section: Ros and Resistance To Fungal Pathogens Of Leavesmentioning
confidence: 98%
“…Microarray results indicate that S. sclerotiorum infection induces the expression of genes encoding components of diverse biological processes, including the jasmonic acid (JA) and ethylene (ET) signaling pathways (Zhao et al, 2007(Zhao et al, , 2009. Recent studies of Arabidopsis (Arabidopsis thaliana) mutants revealed that JA, ET, auxin, abscisic acid, nitric oxide, and reactive oxygen species all contribute to basal resistance against S. sclerotiorum (Guo and Stotz, 2007;Perchepied et al, 2010;Stotz et al, 2011). Conclusions in these studies about the role of the salicylic acid (SA) signaling pathway in resistance to S. sclerotiorum are contradictory (Guo and Stotz, 2007;Perchepied et al, 2010;Wang et al, 2012;Nováková et al, 2014).…”
mentioning
confidence: 99%
“…Recent studies of Arabidopsis (Arabidopsis thaliana) mutants revealed that JA, ET, auxin, abscisic acid, nitric oxide, and reactive oxygen species all contribute to basal resistance against S. sclerotiorum (Guo and Stotz, 2007;Perchepied et al, 2010;Stotz et al, 2011). Conclusions in these studies about the role of the salicylic acid (SA) signaling pathway in resistance to S. sclerotiorum are contradictory (Guo and Stotz, 2007;Perchepied et al, 2010;Wang et al, 2012;Nováková et al, 2014). Nevertheless, these results suggest that the Arabidopsis basal resistance against S. sclerotiorum is complex and involves multiple signaling pathways.…”
mentioning
confidence: 99%